(untitled) (Journal of Population and Development, 2024)
While Nepal is rich in water resources, there are also plenty of water related problems. Issues like water scarcity; improper water allocation, distribution, collection of water fees, farmers’ cooperation, performance of water users association etc give rise to water-induced conflict. As there is a wide range of such issues, this article examines only the conflict of water in the sector of irrigation and its management practices. This article assesses the major dimensions of irrigation management and how these dimensions give rise to conflict using a case study of the Khageri irrigation project (KIP). This study is based on the qualitative design including key informant interviews (KII), focus group discussion (FGD) and participant observation. The informants cover key stakeholders like members of water users associations, elderly farmers, local government officials, etc. Some of the major issues concern to conflict is the denial of riparian rights, repair and maintenance activities related to the canal, resource rights dilemmas, human encroachment to the canal, park control and legal restrictions etc. In addition, impact of climate change is one of the major factors that escalate conflict in the study area. Theory of co-management, Hardin’s tragedy of commons -position, interest, and needs (PIN), the best alternative to a negotiated agreement (BATNA), etc. were used as a theoretical lenses to analyze the findings. Analysis through these theories has further given rise to some other new theoretical models like neo-liberal socioeconomic resource management.